K KAJIAN GULA REDUKSI MENJADI ALKOHOL DARI TANDAN KOSONG KELAPA SAWIT DENGAN SIMULTANEOUS SACCHARIFICATION AND FERMENTATION (SSF): - Widia Rini Hartari; Maryanti Maryanti; Bigi Undadraja (Jurnal Penelitian Pertanian Terapan, 2021)
Alcohol is closely related to daily life. It is used as a solvent or additional substance in the food, industry, pharmacology, laboratory, and beauty sectors. Empty oil palm bunches waste is the potential to process into alcohol because it contains cellulose that can be transformed into sugar, and the sugar is fermented into alcohol. The objective of this research was to find out the reducing sugar and alcohol produced from empty oil palm bunches. This research was done in two stages. The first stage was the preparation of empty oil palm bunches with basal (NaOH) treatment. The second stage included fermentation with cellulose enzyme (Novozymes Yield CL) for 24 hours and then fermented with Saccharomyces cerevisiae for 72 hours. The substrate concentrations to use were 7.5% and 10% and starter concentrations were 10%, 15%, and 20%. Research data were analyzed by using a completely randomized design (CRD) and then followed with the least significant difference (LSD). The result showed that 7.5% substrate addition produced the highest reducing sugar by 3.014% and then 10% substrate produced 2.686% reducing sugar. The alcohol test result showed that 10% substrate and 20% starter were significantly different by 3.5%, and 7.5% and 10% produced the lowest alcohol by 1%.